Research management in Portugal: a quest for professional identity - Trindade, M.; Agostinho, M. (Research Management Review, 2014)
Research managers at science-intensive institutions appear as a continuously evolving group of professionals whose identity is somewhat fragmented, even to themselves. In Portugal, specialized research manager roles have rapidly emerged over the last years alongside the development of a small but consolidated scientific system. In order to get an inside view of the professional identity associated to research management in Portugal, the authors conducted a semi-structured discussion session with a group of professionals. The session aimed to find operational definitions of research management in a broad sense, identifying competencies and skills required to perform such roles, and discuss perspectives on career development in the current scenario. This article departs from the perceptions collected within the group of professionals to inquire about the future environment of the profession.